I am having a hard time with this problem. The only thing I can think to do is change cos(x) to (1-sin^2(x)) but im not even sure how that would help. What step am I missing here?

Results 1 to 3 of 3

- Nov 6th 2008, 01:10 PM #1

- Joined
- Nov 2008
- Posts
- 4

- Nov 6th 2008, 03:51 PM #2

- Nov 6th 2008, 05:08 PM #3

- Joined
- Nov 2008
- Posts
- 4

Thank you. However, I am still having problems.

Sin(4x) * Cos(x) = 0.84

2*Sin(2x)*cos(2x) * cos(x) =0.84

2*2*Sin(x)*cos(x)*(cos^2x-sin^2x)*cos(x) = 0.84

4*sin(x)*cos^2(x)*(cos^2x-sin^2x) = 0.84

sin(x)*cos^2(x)*(cos^2x-sin^2x)=0.21

Forgive me, but I am not sure how to further simplify this problem.